Transcutaneous posterior tibial nerve stimulation versus extended release oxybutynin in overactive bladder patients. A prospective randomized trial. (January 2016) - Manríquez, Valentín; Guzmán, Rodrigo; Naser, Michel; Aguilera, Amalia; Narvaez, Simonie; Castro, Ariel; Swift, Steven; Digesu, G. Alessandro
Abstract: Introduction and hypothesis: The aim of this study was to evaluate the effectiveness of transcutaneous posterior tibial nerve stimulation (T.C. PTNS) versus extended release oxybutynin (E.R.O.) in patients with overactive bladder. Materials and methods: Seventy female patients were randomized to receive either 10 mg E.R.O. daily or T.C. PTNS, using a TENS machine program with the 20 Hz, 200 cycles/s, and normal stimulation setting for two 30-min sessions, each week for a 12-week period. Pre-treatment and after the 12-week intervention, each patient completed a 3-day voiding diary and a self-report quality of life questionnaire (OAB-q). Statistical analysis was performed using Stata V12.1. Results: Sixty-four patients completed the treatment protocol. There were no significant differences between study groups in terms of age, body mass index, past hormone replacement therapy, smoking habits, menopause status, and parity. Prior to treatment, there were also no significant differences in the analysis of the 3-day voiding diary or in the OAB-q questionnaire results. Following the 12-week study, there was a statistically significant reduction in frequency of urination, urgency episodes, and urge incontinent episodes compared to pre-treatment values. However, there were no significant differences in these values between intervention groups after 12-weeks of therapy. There was a similar improvement in OAB-q scores in both treatment groups following therapy, and the T.C. PTNS group showed a statistically significant improvement over the E.R.O. in domain 2 of the OAB-q questionnaire. The other two domains showed similar improvement in both study groups. Conclusion: T.C. PTNS and E.R.O. demonstrated similar improvements in subjects with OAB in a 12-week study.